Analisis Perilaku Nikah Siri Masyarakat Pamekasan Sebelum Akad Nikah di Hadapan Pejabat KUA - Asyhari (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2022)
(This study reveals the fact of the community anomaly, carrying out a serial marriage which is carried out a few days or months before the marriage is officially carried out in front of the official of the Office of Religious Affairs (KUA). There are at least three reasons for the unregistered marriage to be carried out, namely as an anticipation of the wrong assumptions of the public who judge that engagement has consequences such as a marriage contract. Second, avoiding the fall of the bride and groom into acts such as adultery and others. Third, as an effort to hasten the marriage because of concerns about the failure of the wedding procession.)